Implementasi Data Mining Untuk Market Basket Analysis Menggunakan Asosiation Rules Pada Minimarket 212 Mart Batam - Nur Rizky Setia Saragi Rumahorbo; Sasa Ani Arnomo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Data mining is a method of searching for previously unknown information from a large database. The important information found to be valuable and beneficial for the making of a decision. The information gained should be precise and accurate because it was highly influential in decision making as well as the outcome of the decision, as was the information required by the Minimarket 212 Mart Taman Carina Batam. The minimarket is located close to the residents' housing and the school. Minimarket 212 Mart requires an analysis to find out consumer purchasing habits that would later be useful for organizing store layouts, make inventory of product efisien in order for sales transactions to run smoothly also increase sales results in minimarkets. Market basket analys methods can be used to analyze the interrelationship of product that consumers buy at the same time to find out the consumer's purchasing habits. The study successfully found the combination of interrelated products that had the highest support value and confidence value on the combination of Snack, Baverage, Breakfast Food which were to have a 26,7% support value and 100% confidence